Zakonnice-artystki i sztuka nowoczesna w PRL-u wobec aggiornamento - Markowska, Anna (2024)
The article takes up a theme of nuns-artists and modern art in Polish People’s Republic during the aggiornamento. Modernist art in communist Poland didn’t solely evolve within state institutions. The changes spurred by the Vatican Council swiftly permeated nunneries. Religious artists, including those with advanced education like Zofia Wendorff-Serafinowicz, Sister Paula (1905–1989), a Benedictine nun from Żarnowiec; Małgorzata Bogucka (1918–1995), an Ursuline of the Roman Union from Wrocław; Alma Skrzydlewska (1930–2017), affiliated with the Congregation of Franciscan Sisters Servants of the Cross, engaged with the center for the visually impaired Laski near Warsaw; and Julitta Gołębiowska (1933–2011), a Pallottine nun from Gdańsk, swiftly embraced the modernist idiom in their creations. Some of them even ahead of the conclusion of the Vatican II era. Apart from their autonomous or unassisted works of sacred and religious art, the sisters also crafted numerous decorations for festive occasions like Christmas and Easter, adorned altars, curated exhibitions, designed theatrical sets, and produced cards and stationery. The former served liturgy and devotional needs, while the latter, closely related to Miriam Schapiro’s femmage, aimed to deepen mutual friendship and joy within the religious community. Both, moreover, can serve today as evidence of “many modernities.”
Keywords: modernism; artists-nuns; aggiornamento